2021
DOI: 10.3390/agronomy11112279
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Changes Analysis of Soil Properties Associated with Ganoderma boninense Pat. Infection in Oil Palm Seedlings in a Controlled Environment

Abstract: Basal stem rot (BSR) disease of oil palm (Elaeis guineensis Jacq.) spreads through the contact of the plant roots with Ganoderma boninense (G. boninense) Pat. inoculum in the soil. The soil properties can be altered by growing seedlings with or without G. boninense inoculum. In the early stage of infection, the symptoms are difficult to detect. Therefore, an understanding of the environmental soil conditions of the plant is crucial in order to indicate the presence of the fungus. This paper presents an analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Furthermore, healthy seedlings were significantly different from infected seedlings in all parameters in the weekly analysis, according to a Student’s t-test at a 5% significance level. The results of this study suggested that soil MC, EC, and T could be used as indicators of G. boninense infection, particularly for weekly data ( Aziz et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 89%
See 1 more Smart Citation
“…Furthermore, healthy seedlings were significantly different from infected seedlings in all parameters in the weekly analysis, according to a Student’s t-test at a 5% significance level. The results of this study suggested that soil MC, EC, and T could be used as indicators of G. boninense infection, particularly for weekly data ( Aziz et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 89%
“… Aziz et al (2021) detected G. boninense infection in oil palm seedlings using electrical properties. The data for soil moisture content (MC in percent), electrical conductivity (EC in S/cm), and temperature (T in °C) were collected daily using an IoT approach in which the readings from MEC10 (Dalian Endeavour Technology Co., Ltd., Dalian, China) soil sensors were transferred to the ThingSpeak cloud every hour over a 6-month monitoring period using a 3G Internet connection.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several studies have been conducted to investigate the pathogenicity mechanisms, molecular characteristics, and genetic makeup of G. boninense . These studies have explored various aspects, including genomics [ 14 ], metabolomics [ 21 ], soil properties [ 16 ], gene expression [ 89 , 195 ], transformation protocols [ 196 , 197 ], and the role of specific genes and enzymes [ 175 , 198 , 199 ]. By gaining insights into the pathogenicity of G. boninense , researchers aim to develop effective strategies for disease control and to identify potential resistance genes in oil palm [ 200 ].…”
Section: Research On Detection Methods For Basal Stem Rotmentioning
confidence: 99%
“…Ganoderma species break down complex organic compounds, releasing nutrients into the ecosystem and facilitating the recycling of The pathogenicity mechanisms employed by Ganoderma species involve the secretion of various enzymes and toxins that facilitate the invasion and destruction of host tissues, including ligninases, cellulases, proteases, laccases, phytotoxins, and secondary metabolites such as ganoderic acids [14,15]. Furthermore, environmental factors, such as temperature, humidity, and soil characteristics, are critical in Ganoderma infection and disease development [16,17]. Understanding these factors' influence is essential for designing and implementing effective disease management strategies.…”
Section: Ecological Dimensions Of Ganodermamentioning
confidence: 99%
“…When initially infected by the Ganoderma sp. fungus, oil palm plants have no symptoms at all, but when the infection has developed to 60-70%, symptoms begin to appear, characterized by rotting at the base of the tree trunk, then causing inhibition of water and nutrient supply to all parts of the tree which causes the tree to gradually die (Aziz et al, 2021)).…”
Section: Introductionmentioning
confidence: 99%